Research methods and applications in chemical and biological engineering - Pourhashemi, Ali; Deka, Sankar Chandra, 1965-; Haghi, A. K. (Toronto ; [Hackensack?] New Jersey : Apple Academic Press, 2020)
"This research-oriented book consolidates and provides up-to-date experimental methods currently used in research for many branches of chemical and biological engineering. The book surveys essential ideas and research methodologies, concentrating on experiments as used in applications rather than on fine points of rigorous mathematics. Examples of important applications are reviewed in sufficient detail to provide the reader with a critical understanding of context and research methodology. Research Methods and Applications in Chemical and Biological Engineering presents a broad spectrum of chapters in the various branches of chemical and biological engineering, which demonstrate key developments in these rapidly changing fields. Chapters explore the design, development, operation, monitoring, control and optimization of chemical, physical and biological processes. Case studies are included in some chapters, building a real-world connection"--
OCLC-licensed vendor bibliographic record.
Keywords: Chemical engineering -- Research; Bioengineering -- Research; SCIENCE / General; TECHNOLOGY / Engineering / Chemical & Biochemical